The Relationship Between Students’ Interaction And Online Learning Content - Adri Daswin (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
This study aims to identify and understand the relationship between students’ interaction and online learning content. This research method is associative quantitative research, research that produces quantitative data which will later be used for processing survey data. obtained through observation and literature study. The results showed that the highest average value is found in the items "learning content presented can improve student understanding" and "I use the material provided for more meaningful learning" with the acquisition of 4.32 and 4.28. This data shows that students strongly agree that the learning content presented by the teacher can improve their understanding and they use the learning content for more meaningful learning. The lowest average score on the item "I apply the learning content that I get to problem solving" with an average score of 3.87. This illustrates that students are still lacking in the use of learning content in solving problems. Overall, from 8 question items related to student interaction and online learning content, an average score of 4.14 was obtained in the high category.